2021
DOI: 10.1186/s12917-020-02709-5
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin treatment modulates chemoresistance and affects the cell cycle in two canine mammary tumour cell lines

Abstract: Background Doxorubicin (DOX) is widely used in both human and veterinary oncology although the onset of multidrug resistance (MDR) in neoplastic cells often leads to chemotherapy failure. Better understanding of the cellular mechanisms that circumvent chemotherapy efficacy is paramount. The aim of this study was to investigate the response of two canine mammary tumour cell lines, CIPp from a primary tumour and CIPm, from its lymph node metastasis, to exposure to EC50(20h) DOX at 12, 24 and 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…This is in contrast to what was observed in histological sections of brain microvessels, where the majority of cells expressing vWF co-stained with P-gp or BCRP. It has been reported that P-gp and BCRP levels are linked to cell cycle and p53 expression [ 54 , 55 ]. It is possible that in vitro conditions may impose greater differences in cell cycle phases compared to the in vivo conditions and may, therefore, explain the lack of P-gp and BCRP staining in a small number of vWF-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to what was observed in histological sections of brain microvessels, where the majority of cells expressing vWF co-stained with P-gp or BCRP. It has been reported that P-gp and BCRP levels are linked to cell cycle and p53 expression [ 54 , 55 ]. It is possible that in vitro conditions may impose greater differences in cell cycle phases compared to the in vivo conditions and may, therefore, explain the lack of P-gp and BCRP staining in a small number of vWF-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation was demonstrated by the silencing of ATF6, as shutdown of UPR activation led to a drastic increase in DOXO-induced damage. A potentially protective role of the UPR has been widely reported in the scientific literature [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information demonstrating direct regulation of MDR transporters by nutrients. However, MDRs do interact with a number of substrates which may be derived directly from the diet, and or/dietary components may influence the production/levels of substrates and other molecules that interact directly with MDRs, as seen with inflammation (and thus, metainflammation)[22], and cell cycle stage and p53 expression[51, 52]. To address this, we first explored whether and how maternal gut morphology adapts to the spectrum of malnutrition, as intestinal architecture and morphology may influence cellular function.…”
Section: Discussionmentioning
confidence: 99%